The Meaning Of Nutmeg And Clove North Maluku In Popular Culture - Jerry Dounald Rahajaan (Balong International Journal of Design, 2018)
AbstractPhilosophical meaning contained in nutmeg and clove is an interpretation of inter-relationships between language, culture and cognition with the theory of Cognitive Anthropology which is analyzed by visual structure in the culture of Ternate’s People (North Maluku). In Cognitive Anthropology Perspective of North Maluku people (Ternate), there are studies of Interpretation of Nutmeg and Clove which departs from the backgrounds of the people of North Maluku (Ternate), as well as the philosophy associated with the ecological community of Ternate (North Maluku). In this study there are some components examined including: Nutmeg and Clove treatment period, the period before harvesting the Nutmag, nutmeg and clove harvest time, the drying and sale time, this is an interpretation of the nutmeg and cloves into Jujaro and Ngungare philosophy of Ternate (North Maluku). The purpose of this journal is to convey the meaning of Nutmeg and Clove in philosophy of North Maluku people (Ternate) which is understood by generations and becomes verbal tradition in its delivery in the form of immortal truth meaning. This paper is more focused on visual analysis of nutmeg and clove concept with reference to the interpretation theory of Cognitive Anthropology approach from the native society. As a result, this Journal discusses the visual analysis focused on the philosophical meaning in the concept of Nutmeg and Clove associated with the Jujaro and Ngungare meaning, so that it is synergy with the ecological community which is viewed nutmeg and cloves as society commodity, and its contribution as a model for studies in theory of Interpretation and Cognitive Anthropology in a social order.Keywords— Nutmeg and Clove, Ternate (North Maluku), Theory of Interpretation.